If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -2c + 6c = -29 Combine like terms: -2c + 6c = 4c 9 + 4c = -29 Solving 9 + 4c = -29 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4c = -29 + -9 Combine like terms: 9 + -9 = 0 0 + 4c = -29 + -9 4c = -29 + -9 Combine like terms: -29 + -9 = -38 4c = -38 Divide each side by '4'. c = -9.5 Simplifying c = -9.5
| -7n-36=-n-3(5n+3) | | 12x+2-3x=10-x+2 | | 2(x+7)+8=3(x+6)+9 | | 40=4u+8 | | (0.02)3= | | V=3.14r^2(4r)+3.14r^2(3) | | 3(x+5)-x=11+4(x-1) | | 8=8-7x-x | | 9x+4y=-16 | | y-17=19 | | -3x^3=13x^2+10 | | 22p+13-2p=73 | | 11.62y-92.96+3.32y=3.32y-26.56+26.56 | | 2(153-x)=324 | | n+4n-n-1= | | 2(158-x)=324 | | -38+38x=94+36x | | -2(-6n+1)=4n+30 | | z^2-8z-884=0 | | 4=0.4(3b-5) | | 1=-c-4 | | 14+[3(6x-15)-5]=5x-1 | | 10+3y=5y-2 | | -7(x-2)=-10x+5+3x | | 3x+5=-3(9x+1) | | m+4n-4p+2n+p-zm= | | 19x-7=8+15x | | 4y+9=2y-1 | | 4y+9=2y-1 | | -2(7K+4)+9=-3 | | n/3-9=-7 | | -5(x-3)+8x=25+5x |